Obstructive respiratory failure in cicatricial pemphigoid. Issue 7 (July 1989) - de Carvalho, C R; Amato, M B; Da Silva, L M; Barbas, C S; Kairalla, R A; Saldiva, P H
Abstract : A 20 year old woman died of respiratory failure due to cicatricial pemphigoid of the trachea and bronchi. This is the first case with the lower airways affected to be reported.